2005
DOI: 10.1021/ol051155k
|View full text |Cite
|
Sign up to set email alerts
|

Kadsuphilactones A and B, Two New Triterpene Dilactones from Kadsura philippinensis

Abstract: [structure: see text]. Two novel triterpene dilactones, kadsuphilactones A (1) and B (2), were isolated from the Taiwanese medicinal plant Kadsura philippinensis. The structures of 1 and 2 were elucidated on the basis of extensive spectroscopic methods, including two-dimensional NMR techniques, and confirmed by X-ray crystallographic analysis. Kadsuphilactone B (2) exhibited in vitro anti-HBV activity with IC(50) values of 6 microg/mL by HBsAg enzyme immunoassay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Some of the seco -cycloartanes have reported to have anti-HIV-1 activity [29] and anti-HBV (hepatitis B virus) activity [30]. The earliest example was nigranoic acid from stems of Schisandra sphaerandra that has been demonstrated to be capable of inhibiting HIV viral reverse transcriptase with IC 50 = 74.1  μ g/mL [31].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the seco -cycloartanes have reported to have anti-HIV-1 activity [29] and anti-HBV (hepatitis B virus) activity [30]. The earliest example was nigranoic acid from stems of Schisandra sphaerandra that has been demonstrated to be capable of inhibiting HIV viral reverse transcriptase with IC 50 = 74.1  μ g/mL [31].…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical investigations on species of the family Schisandraceae have revealed that they are rich sources of lignans, which possessed various beneficial pharmacological effects, such as antitumor, 1 cytotoxic, [2][3][4] anti-HIV, 5,6 antioxidative, 7,8 antihepatitis, 9 and hepatoprotective effects. 1 Schisandra propinqua var.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the other Me group at 0.89 (d, J ¼ 6.8) was assigned to Me (17) irreproachably. The HMBC correlations from one OÀCH 2 ÀO group (d(H) 5.93) to C(12) and C (13), from the other OÀCH 2 ÀO group (d(H) 6.00) to C(2) and C(3), and from two MeO groups to C(1) and C (14) indicated the arrangement of the substituents on the biphenyl rings of 1 was the same as that of gomisin R (5) [17]. The location of the two MeO groups was further confirmed by the ROESY correlations (Fig.…”
mentioning
confidence: 99%